Destination managament in Hungarian tourism - Dávid , Lóránt; Tőzsér, Anett (Applied Studies in Agribusiness and Commerce, 2009)
The principle of the regional concentration – as one of the important means of regional competitiveness – and the cooperations being organised more consciously have big parts in the development and operation of the tourist destination management. The principle of complexity is emphasised differently that means, on the one hand, the more effective use of the connection possibilities of tourism to other branches, on the other hand, it takes for granted the development of the background infrastructure supporting tourism more intensively beside the development of the tourist infrastructure. The basic principle of the competitive developments are the sustainable developments and the innovative approach. Tourist destination can be identified with the tourist suppl (product) from the elements of the tourist system: the tourist supply and the tourist destination are consisting just of the same elements. The difference is that the tourist product can be only one product and destination can be characterised as a complex pile of attractions and services being in connection with each other. The cooperation of the characters of destination are organised by the tourist value chain of which elements are the experiences in connection with the formation of the image, preparation of travel, travel, destination, return from the point of view of the tourist and the service providers of destination. Services of different level provided by the suppliers can influence the opinion and experience of the tourist in connection with destination negatively. The independent destination management system with suitable competence and specialists, running a coordinating activity can make a connection between the tourist and the receiving area.